Research on Evaluation System of Short Message Service - Hong Li; Wenhong Zhou; Kai Qu; Siyuan Wu; Sizhong Chen; Qing Li (Dianxin kexue)
For the comprehensive objective assessment of short message service quality, a set of evaluation system of short message service was put forward. A part of the evaluation index was analyzed, and the rationality of related indexes, the development and construction of short message corresponding evaluation system, and the network application were briefly introduced. Through construction and operation of system, the short message service quality evaluation was implemented.